Assessing the impact of AI-driven adaptive learning platforms on student engagement, motivation, confidence and perception on feedback in clinical history-taking - Sukiman, Hamzah; Amjad, Nasser Mohammad (UKM Press, 2024)
Introduction: Undergraduate medical students typically report challenges in history-taking during their clinical years. Artificial Intelligence (AI)-driven adaptive learning platforms have the potential to enhance the experience by providing personalized feedback.